Nz'crunchies / Nur Syazwina Atasha Azman - Azman, Nur Syazwina Atasha (2022)
NZ'Crunchies is the one of the bumiputera product brands for NZ'Frozen Industries sdn bhd which is registered under the companies commission of Malaysia (SSM) and is wholly need. the holding company of NZ crunchies is located at lot E1 SME Industrial Complex, 15 jalan Tabana, Tampoi industrial Estate 80350 Johor. NZ crunchies are snack made from poppy skin and coated with a variety of flavour of this century's delicious and viral option. Among the flavours served are cheese primo golden salted egg, savory chicken, korean bbq, chocolate supreme, milky matcha, butter toast. these snacks are suitable for all group can be used as snack, food to entertain guest and snack to fill an empty stomach.